Experience building and developing Korean internet of things (IoT) and lessons learned for Vietnam - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The article uses the concept of “national absorptive capacity” to build a framework to analyze Korea’s experience in building and developing the internet of things (IoT) with 4 pillars: (i) General readiness of the economy; (ii) Takeoff-ready factors; (iii) Transformational factors; (iv) and Drivers for innovation and creativity. From Korea’s experience, the article proposes some suggestive lessons for Vietnam in building and developing the internet of things in accordance with the context of developing countries. Code: 21092501